2022
DOI: 10.3201/eid2813.220711
|View full text |Cite
|
Sign up to set email alerts
|

Extending and Strengthening Routine DHIS2 Surveillance Systems for COVID-19 Responses in Sierra Leone, Sri Lanka, and Uganda

Abstract: The COVID-19 pandemic challenged countries to protect their populations from this emerging disease. One aspect of that challenge was to rapidly modify national surveillance systems or create new systems that would effectively detect new cases of COVID-19. Fifty-five countries leveraged past investments in District Health Information Software version 2 (DHIS2) to quickly adapt their national public health surveillance systems for COVID-19 case reporting and response activities. We provide background on DHIS2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In addition, linkages between point of entry screening and health service delivery systems were enhanced using a standard operating procedure which was developed to facilitate referral system. At health facilities, digital applications for COVID-19 were developed in partnership with University of Dar es Salaam to improve case base reporting at health facilities and facilitate contact tracing ( 27 ).…”
Section: Country Responses For Effective Covid-19 Pandemic Managementmentioning
confidence: 99%
“…In addition, linkages between point of entry screening and health service delivery systems were enhanced using a standard operating procedure which was developed to facilitate referral system. At health facilities, digital applications for COVID-19 were developed in partnership with University of Dar es Salaam to improve case base reporting at health facilities and facilitate contact tracing ( 27 ).…”
Section: Country Responses For Effective Covid-19 Pandemic Managementmentioning
confidence: 99%
“…CDC has provided longstanding support to strengthen surveillance, health information, and laboratory systems globally. Examples of such platforms used during the COVID-19 pandemic include the early warning and response surveillance system ( 1 ); respiratory ( 2 ), influenza ( 3 ), and acute febrile illness surveillance systems ( 4 ); global health security–supported information systems (e.g., District Health Information Software, version 2 [DHIS2]) ( 5 ); and PEPFAR-supported HIV and tuberculosis (TB) information systems ( 6 , 7 ). Respiratory disease surveillance guidance was developed for COVID-19 in 9 temporary camps for displaced persons along the Thailand–Myanmar border, showing that such systems can be effective during pandemics ( 2 ).…”
Section: Surveillance Information and Laboratory Systemsmentioning
confidence: 99%
“…CDC collaborated with MOH and partners to leverage existing acute febrile illness surveillance systems in 5 countries to collect and generate COVID-19 data needed for action ( 4 ). Kinkade et al described 3 countries’ experience strengthening surveillance systems and reporting using DHIS2 for COVID-19 ( 5 ). Mirza et al showed how health information systems for HIV and TB were modified for COVID-19 ( 6 ).…”
Section: Surveillance Information and Laboratory Systemsmentioning
confidence: 99%
“…Currently, other countries are gradually using existing surveillance platforms to identify other pathogens, especially in the context of COVID-19. 3 , 4 Much progress has been made in building capacities nationally, regionally, and globally to protect the world from influenza. 5 This progress can be used as a basis and an example for monitoring other epidemic-prone and pandemic-prone pathogens, especially those of respiratory origin.…”
mentioning
confidence: 99%